Mouse-adapted MERS coronavirus causes lethal lung disease in human DPP4 knockin mice - Li, Kun (Proc Natl Acad Sci U S A, 2017)
The Middle East respiratory syndrome (MERS) emerged in Saudi Arabia in 2012, caused by a zoonotically transmitted coronavirus (CoV). Over 1,900 cases have been reported to date, with ∼36% fatality rate. Lack of autopsies from MERS cases has hindered understanding of MERS-CoV pathogenesis. A small animal model that develops progressive pulmonary manifestations when infected with MERS-CoV would advance the field. As mice are restricted to infection at the level of DPP4, the MERS-CoV receptor, we generated mice with humanized exons 10–12 of the mouse Dpp4 locus. Upon inoculation with MERS-CoV, human DPP4 knockin (KI) mice supported virus replication in the lungs, but developed no illness. After 30 serial passages through the lungs of KI mice, a mouse-adapted virus emerged (MERS(MA)) that grew in lungs to over 100 times higher titers than the starting virus. A plaque-purified MERS(MA) clone caused weight loss and fatal infection. Virus antigen was observed in airway epithelia, pneumocytes, and macrophages. Pathologic findings included diffuse alveolar damage with pulmonary edema and hyaline membrane formation associated with accumulation of activated inflammatory monocyte–macrophages and neutrophils in the lungs. Relative to the parental MERS-CoV, MERS(MA) viruses contained 13–22 mutations, including several within the spike (S) glycoprotein gene. S-protein mutations sensitized viruses to entry-activating serine proteases and conferred more rapid entry kinetics. Recombinant MERS(MA) bearing mutant S proteins were more virulent than the parental virus in hDPP4 KI mice. The hDPP4 KI mouse and the MERS(MA) provide tools to investigate disease causes and develop new therapies.